Area Agencies on Aging - Fatima Perkins; Andrzej Klimczuk (Encyclopedia of Gerontology and Population Aging, 2020)
An area agency on aging (AAA) is a public or private nonprofit organization designated by the state to address the needs and concerns of all older persons at the regional and local levels in the United States (Administration for Community Living (ACL) 2019). AAAs have a successful history of developing, coordinating, and implementing comprehensive networks of services and programs that enrich communities and the lives of older adults. AAAs were established through a provision of the Older Americans Act (OAA 1965), which was signed into law by President Lyndon B. Johnson. Specifically, AAAs were created with the 1973 reauthorization of the OAA. AAAs create the infrastructure to execute comprehensive long-term support services that ensure the independence of older adults.
Keywords: J14; J18; 300; ageing; Resources for older people